DESIGN OF HEAT TRANSFER PRACTICUM SET BASED ON ARDUINO MICROCONTROLLER WITH DATA LOGGER: RANCANGAN SET PRAKTIKUM TRANSFER KALOR BERBASIS MIKROKONTROLER ARDUINO DENGAN DATA LOGGER - Siti Maryam Ahlamya; Hadi Nasbey; Upik Rahma Fitri (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
This study aims to design a heat transfer experiment set based on an Arduino microcontroller with a data logger. This research employs the Research and Development method, utilizing a 4D research model (Define, Design, Develop, and Disseminate) that is limited to the Design stage. Initial data collection during the Define stage involved distributing questionnaires to students, interviewing teachers, observing school laboratories, and conducting a literature review. The data obtained were analyzed and used as a guide to determine the material concepts, learning objectives, and learning activities. Based on the data analysis, there is a need for an experiment set on heat transfer that can continuously record data. During the Design stage, the researchers selected the format and type of learning media, developed a test outline, and designed an experiment set that accommodates the identified learning needs. The result is a design for a heat transfer experiment set based on an Arduino microcontroller with a data logger, providing a solution to the learning needs identified in the Define stage. The design consists of a physical experiment tool and a computer application